Sustaining education for environmental professionals. Issue 4 (2nd October 2022) - Thomas, Ian
ABSTRACT: The evolution of universities in Australia is nothing new; however, a range of social and economic pressures have been exacerbated by the COVID-19 pandemic. These pressures are leading to changes, for example greater use of electronic media for teaching, which will affect the delivery of teaching programs. Effects on those programs providing education for environmental professionals could well impact whether the graduates achieve the capabilities expected by the profession, and needed by society. These capabilities have much in common with those sought by a range of professions and disciplines, and the employability agenda promoted by universities. Hence, promotion of learning approaches associated with educating environmental professionals could be of value to universities generally. The review of these aspects indicates the need for the profession to formulate approaches to ensure that education of environmental professionals in Australia continues to achieve those capabilities that have been identified. Effort directed this way could assist in maintaining or enhancing, achieving capabilities of the graduates of environmental and sustainability programs. Such effort would also facilitate all graduates to develop the generic capabilities expected by employers and infuse sustainability across all disciplines with a sustainability leaning.